Ethics in Gene Editing: A Narrative Literature Review - I Made Diana (HM Publisher, 2021)
Gene editing is the process of making precise, intentional changes to the DNA sequence of an organism, including humans, animals, and plants. However, there are always ethical questions to address, especially when the manipulation involves the human genome. This literature review aimed to describe the ethics of gene editing and its application. There is currently an urgent need to actively pursue those conversations as commercial gene sequencing and editing technologies have become more accessible and affordable. Gene editing has enormous potential both as a research tool and a therapeutic intervention. While other types of gene editing are relatively uncontroversial, gene editing has been strongly resisted. In conclusion, gene editing research can be conducted safely in ways that carry manageable and reasonable risks.